Enhancing the Microhardness of Coatings Produced by Cold Gas Dynamic Spraying through Multi-Reinforcement with Aluminum Powders Containing Fullerenes and Aluminum Nitride - Artemiy Aborkin; Dmitry Babin; Leonid Belyaev; Dmitry Bokaryov (Journal of Manufacturing and Materials Processing, 2023)
Coatings with high hardness were successfully obtained using low-pressure cold spray (LPCS) technology from nanocrystalline powders based on the aluminum alloy AlMg6, which were multi-reinforced with 0.3 wt.% fullerenes and 10–50 wt.% AlN. The powders were synthesized through a two-stage high-energy ball milling process, resulting in a complex mechanical mixture consisting of agglomerates and micro-sized ceramic particles of AlN. The agglomerates comprise particles of the nanocomposite material AlMg6/C60 with embedded and surface-located, micro-sized ceramic particles of AlN. Scanning electron microscopy and EDS analyses demonstrated a uniform distribution of reinforcing particles throughout the coating volume. An X-ray diffraction (XRD) analysis of the coatings revealed a change in the predominant orientation of matrix alloy grains to a more chaotic state during deformation over the course of cold gas dynamic spraying. A quantitative determination of AlN content in the coating was achieved through the processing of XRD data using the reference intensity ratio (RIR) method. It was found that the proportion of transferred ceramic particles from the multi-reinforced powder to the coating did not exceed ~65%. Experimental evidence indicated that LPCS processing of mono-reinforced nanocrystalline powder composite AlMg6/C60 practically did not lead to the formation of a coating on the substrate and was limited to a monolayer with a thickness of ~10 µm. The microhardness of the monolayer coating obtained from the deposition of AlMg6/C60 powder was 181 ± 12 HV. Additionally, the introduction of 10 to 50 wt.% AlN into the powder mixture contributed to the enhancement of growth efficiency and an increase in coating microhardness by ~1.4–1.7 times. The obtained results demonstrate that the utilization of agglomerated multi-reinforced powders for cold gas dynamic spraying can be an effective strategy for producing coatings and bulk materials based on aluminum and its alloys with high microhardness.